2020
DOI: 10.1080/07391102.2020.1819883
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential inhibitors of SARS-CoV-2 main protease and spike receptor from 10 important spices through structure-based virtual screening and molecular dynamic study

Abstract: The outbreak of novel coronavirus disease (COVID-19) caused by SARS-CoV-2 poses a serious threat to human health and world economic activity. There is no specific drug for the treatment of COVID-19 patients at this moment. Traditionally, people have been using spices like ginger, fenugreek and onion, etc. for the remedy of a common cold. This work identifies the potential inhibitors of the main protease (M pro) and spike (S) receptor of SARS-CoV-2 from 10 readily available spices. These two proteins, S and M p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 108 publications
(110 reference statements)
1
39
0
Order By: Relevance
“…Structure-based virtual screening of FDA-approved drug bank database that resulted in 20 hits against 3CLpro was performed by Chatterjee, Shilpa, et al ( Chatterjee et al, 2020 ) Recently, Sen et al virtually screened 10 important spices to identify potential inhibitors for both main protease and spike with the support of molecular dynamic simulations. ( Sen et al, 2020 ). Finally, Huynh et al, explored mechanisms of clinically oriented SARS-CoV-2 inhibitors including naturally occurring rutin as main protease inhbitors.…”
Section: Introductionmentioning
confidence: 99%
“…Structure-based virtual screening of FDA-approved drug bank database that resulted in 20 hits against 3CLpro was performed by Chatterjee, Shilpa, et al ( Chatterjee et al, 2020 ) Recently, Sen et al virtually screened 10 important spices to identify potential inhibitors for both main protease and spike with the support of molecular dynamic simulations. ( Sen et al, 2020 ). Finally, Huynh et al, explored mechanisms of clinically oriented SARS-CoV-2 inhibitors including naturally occurring rutin as main protease inhbitors.…”
Section: Introductionmentioning
confidence: 99%
“…According to available evidence, a spike mutant called spike D614G is more prevalent in some areas, especially in European countries, and has a higher mortality rate (Becerra-Flores & Cardozo, 2020 ; Eaaswarkhanth et al, 2020 ; Koyama et al, 2020 ). Although it was suggested that replacement of Asp614 (native form) with Gly reduces the affinity of the spike to bind to the hACE2 through surface, infectivity of the spike D614G is higher than native one (Sen, 2020 ). The present study aims to investigate the structural and molecular properties of mutant D614G by employing bioinformatics and molecular dynamics (MD).…”
Section: Introductionmentioning
confidence: 99%
“…A number of Ayurvedic herbs have been used for management of SARS-CoV-2 infection (Shree et al, 2020 ; Tripathi et al, 2020 ). Some of the key Indian herbs such as Ashwagandha, Tulsi, Giloy and Turmeric contain several active phytochemicals which selectively bind with various SARS-CoV-2 vital targets (Chowdhury, 2020 ; Emirik, 2020 ; Kumar et al, 2020 ; Sen et al, 2020 ; Shree et al, 2020 ; Tripathi et al, 2020 ). The phytochemicals from several Indian spices have also shown possible beneficial effect against SARS-CoV-2 (Sen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of AYUSH (Ayurvedic, Yoga and Naturopathy, Unani, Siddha and Homeopathy), Government of India, has recommended the use of Kadha for boosting the immunity and reducing inflammation during COVID-19 crisis (The Ministry of AYUSH 2020). To manage COVID-19 crisis, several Indian Ayurvedic herbs, spices and their active phytochemicals have been explored for their possible prophylactic and therapeutic use against COVID-19 (Chowdhury, 2020 ; Emirik, 2020 ; Kumar et al, 2020 ; Sen et al, 2020 ; Shree et al, 2020 ; Swargiary et al, 2020 ; Tripathi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%